2016
DOI: 10.1007/s00418-015-1397-0
|View full text |Cite
|
Sign up to set email alerts
|

KCC2 knockdown impairs glycinergic synapse maturation in cultured spinal cord neurons

Abstract: Synaptic inhibition in the spinal cord is mediated mainly by strychnine-sensitive glycine (GlyRs) and by γ-aminobutyric acid type A receptors (GABAAR). During neuronal maturation, neonatal GlyRs containing α2 subunits are replaced by adult-type GlyRs harboring α1 and α3 subunits. At the same time period of postnatal development, the transmembrane chloride gradient is changed due to increased expression of the potassium-chloride cotransporter (KCC2), thereby shifting the GABA- and glycine-mediated synaptic curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Simultaneously, the intracellular chloride concentration is reduced due to chloride extrusion by the KCC2 and KCC3 chloride-potassium co-transporters to the point where it supports efficient synaptic inhibition (47). A recent study that inhibited KCC2 function in cultured spinal neurons during this period found that the elevated chloride concentration reduced the number and size of ␣1 GlyR dendritic clusters without affecting neighboring ␣2 GlyR clusters (48). Concomitantly, glycinergic miniature IPSCs were reduced in amplitude and frequency although GABAergic IPSCs were not affected.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the intracellular chloride concentration is reduced due to chloride extrusion by the KCC2 and KCC3 chloride-potassium co-transporters to the point where it supports efficient synaptic inhibition (47). A recent study that inhibited KCC2 function in cultured spinal neurons during this period found that the elevated chloride concentration reduced the number and size of ␣1 GlyR dendritic clusters without affecting neighboring ␣2 GlyR clusters (48). Concomitantly, glycinergic miniature IPSCs were reduced in amplitude and frequency although GABAergic IPSCs were not affected.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we considered whether a neurodevelopmental defect may result in fewer glycinergic synapses in adult motor neurons. This idea stemmed from a recent study that concluded that an elevated intracellular chloride concentration late during development ablates α1β glycinergic synapses but spares GABAergic synapses (Schwale et al, 2016). As this mechanism satisfies all our considerations, we propose it is primarily responsible for the gain-offunction hyperekplexia phenotype.…”
supporting
confidence: 61%
“…Simultaneously, the intracellular chloride concentration is reduced due to chloride extrusion by the KCC2 and KCC3 chloride-potassium co-transporters to the point where it supports efficient synaptic inhibition (48). A recent study that inhibited KCC2 function in cultured spinal neurons during this period found that the elevated chloride concentration reduced the number and size of a1 GlyR dendritic clusters without affecting neighbouring a2 GlyR clusters (49).…”
Section: Proposed Mechanism Of Hyperekplexia By Gain-of-function Glramentioning
confidence: 99%
“…In addition, enhancement of KCC2 restores spinal inhibition and reserves neuropathic pain (58). KCC2 knockdown impairs glycinergic synapse maturation in cultured spinal cord neurons (59). Taken together, decrease of KCC2 destroyed chloride homeostasis and affected the inhibition of inhibitory neurons.…”
Section: Volume 3 May 2016mentioning
confidence: 99%